INTEGRATED WRITING IN DIFFERENTIATED ESP COURSE AT TECHNICAL UNIVERSITY - Synekop, Oksana; Lytovchenko, Iryna (LLT Journal: A Journal on Language and Language Teaching, 2024)
The current study aims to investigate the effectiveness of teaching integrated writing using differentiated tasks in an ESP university course. The mixed research method was used in the study. Eighty IT students of Igor Sikorsky Kyiv Polytechnic Institute voluntarily took part in the study in the 2022-2023 academic year. The integrated writing involved reading-writing, listening-writing, and reading-listening-writing tasks. The differentiation according to the level of foreign language proficiency and the learning style of IT students was implemented. The results showed that the percentage of IT students who improved their integrated writing skills due to the differentiation of foreign language proficiency level and the learning style in the first group was bigger than in the second one. It was concluded that teaching integrated writing with a focus on learners’ differentiation is a means of simultaneous development of reading-writing, listening-writing, and reading-listening-writing skills in the professional context. It also helps to diversify ESP instruction at technical universities.